Clear cell sarcoma of the esophagus: A rare location. Issue 2 (22nd December 2019) - Yahyaoui, Yosra; Zenzri, Yosr; Behi, Khalil; Boujelbene, Nadia; Mokrani, Amina; Abbas, Imen; Mrad, Karima; Mezlini, Amel
Abstract: Clear cell sarcoma of the esophagus is very rare. The etiology of this neoplasm remains unknown. Confirmed diagnosis requires histopathology with immunochemistry and molecular study. CCS typically shows highly aggressive behavior with a high rate of local recurrence, metastases, and death from disease. Abstract : Clear cell sarcoma of the esophagus is very rare. The etiology of this neoplasm remains unknown. Confirmed diagnosis requires histopathology with immunochemistry and molecular study. CCS typically shows highly aggressive behavior with a high rate of local recurrence, metastases, and death from disease.